PERAN LEMBAGA KEUANGAN SYARI’AH DI MASA PANDEMI COVID-19 DALAM MERANGKUL UMKM (Studi Kasus pada KSPPS BMT Pratama Cahaya Mentari Rawalumbu) - WAHIDIN MUSTA’IN BILLAH (DIRHAM Jurnal Ekonomi Islam, 2021)
Since the time of the Covid-19 Pandemic, economic sectors have implemented work from home (WFH) policy as well as the world of education organizing school activities and lectures online. This condition encourages the public to comply with government directions so that there is no wider spread of Covid-19. With the existence of restrictions on community activities in various fields, those who really feel the impact are the entrepreneurs of the Micro, Small, and Medium Enterprises (MSMEs). This research uses qualitative research methods with primary and secondary data. This study finds that it is necessary to have the role of financial institutions that can support the capital of MSMEs. Sharia Financial Institutions (LKS) are institutions engaged in the financial sector, both collection and financing as well as operations in other financial services. As an LKS, in carrying out its role, KSPPS BMT Pratama Cahaya Mentari has the potential to run with extraordinary support from Muhammadiyah residents and the local environment. In addition, to support from the community, BMT PCM has strong pillars, including diverse and solution products and services. The latest system of procedures, prudence, and compliance with SDI's sharia and integrity, professional and competent leadership, infrastructure that seeks to be reliable, sturdy and adaptive, safe, and directed. The implementation of KSPPS BMT Pratama Cahaya Mentari has been running 51%.